Supramolecular self-assembly of the γ-cyclodextrin and perfluorononanoic acid system in aqueous solution. Issue 5 (16th December 2020) - Zhang, Juan; Liu, Cuiting; Hu, Xinyue; Lv, Qichao; Zhang, Hongsheng; Pi, Benxiang; Yang, Zihao; Lin, Meiqin
Abstract : Schematic representation of aggregates formed by the self-assembly of PFNA@γ-CD complexes. Abstract : Recently, inclusion complexes formed from cyclodextrins (CDs) and surfactants have been found to play complex and important roles in supramolecular self-assembly. In this work, the self-assembly of perfluorononanoic acid (PFNA)/γ-cyclodextrin (γ-CD) in aqueous solution was investigated. The sole PFNA solution assembled into spherical uni-lamellar vesicles under certain concentrations as revealed by freeze-fracture transmission electron microscopy (FF-TEM) images. Interestingly, when γ-CD was added into the PFNA solution, one novel kind of cyclodextrin-based hydrogel with a crystal-like structure was obtained. The morphology of the hydrogels was inerratic parallel hexahedron or regular hexahedron as revealed by optical microscopy and scanning electron microscopy (SEM) measurements. Furthermore, the hydrogels were transformed into crystalline precipitates, which were composed of highly uniform tetragonal sheets with excellent crystallinity and homogeneous size distribution just by changing the γ-CD concentration. More amazingly, the crystal-like hydrogels were sensitive to shear and switched to solutions in their morphology with bar-like and rod-like aggregates and smaller square sheets under different shear rates, and the hydrogel-solution transition behavior was a reversable process. 1 H NMR, Fourier transform infrared (FT-IR) and wide-angle X-ray diffraction (WXRD) measurements were performed to lead us to propose the formation mechanism of the above aggregates. Hopefully, our studies will cast new light on the fundamental investigations into the self-assembly of supramolecular systems of fluorinated surfactants and CD molecules and provide a new idea for smart material design.